The Critical Impact of Material and Process Compatibility on the Active Layer Morphology and Performance of Organic Ternary Solar Cells. Issue 2 (19th November 2018) - Kim, Joo‐Hyun; Schaefer, Charley; Ma, Tingxuan; Zhao, Jingbo; Turner, Johnathan; Ghasemi, Masoud; Constantinou, Iordania; So, Franky; Yan, He; Gadisa, Abay; Ade, Harald
Abstract: Although ternary solar cells (TSCs) offer a cost‐effective prospect to expand the absorption bandwidth of organic solar cells, only few TSCs have succeeded in surpassing the performance of binary solar cells (BSCs) primarily due to the complicated morphology of the ternary blends. Here, the key factors that create and limit the morphology and performance of the TSCs are elucidated. The origin of morphology formation is explored and the role of kinetic factors is investigated. The results reveal that the morphology of TSC blends considered in this study are characterized with either a single length‐scale or two length‐scale features depending on the composition of the photoactive polymers in the blend. This asymmetric morphology development reveals that TSC blend morphology critically depends on material compatibility and polymer solubility. Most interestingly, the fill factor (FF) of TSCs is found to linearly correlate with the relative standard deviation of the fullerene distribution at small lengths. This is the first time that such a correlation has been shown for ternary systems. The criteria that uniform sized and highly pure amorphous domains are accomplished through the correct kinetic path to obtain a high FF for TSCs are specifically elucidated. The findings provide a critical insight for the precise design and processing of TSCs. Abstract : Linear correlation of fill factor and relative standard deviation of fullerene distribution reveals that a ternary blend morphology with a uniform and pure mixed amorphous domain is required to achieve efficient ternary solar cells. This is achieved by the right kinetic path, controlled by the material and process compatibility.